Lightweight mobile stick-type water-based triboelectric nanogenerator with amplified current for portable safety devices. Issue 1 (31st December 2022) - Cha, Kyunghwan; Chung, Jihoon; Heo, Deokjae; Song, Myunghwan; Chung, Seh-Hoon; Hwang, Patrick T.J.; Kim, Dongseob; Koo, Bonwook; Hong, Jinkee; Lee, Sangmin
ABSTRACT: Due to its abundance, mechanical energy is a promising ambient energy source. Triboelectric nanogenerators (TENGs) represent an effective mechanical energy harvesting method based on the use of contact electrification. The existing liquid-based TENGs can operate robustly without surface damage; however, the output of these TENGs is considerably smaller than that of solid-based TENGs. Notably, liquid-based TENGs in which the liquid directly contacts the conductive material can produce an electrical current of more than few mA. However, the liquid reservoir must have an adequate volume, and sufficient space must be provided for the liquid to move for generating the electrical output. To ensure a compact and lightweight design and produce electrical output in the low input frequency range, we introduce a mobile stick-type water-based TENG (MSW-TENG). The proposed MSW-TENG can generate an open-circuit voltage and closed-circuit current of up to 710 V and 2.9 mA, respectively, and be utilized as self-powered safety device. The findings of this study can promote the implementation of TENGs in everyday applications. Graphical Abstract: uf0001